Do submucous myoma characteristics affect fertility and menstrual outcomes in patients underwent hysteroscopic myomectomy? - Ahmed Namazov; Resul Karakus; Ezgi Gencer; Hamdullah Sozen; Levent Acar (Shahid Sadoughi University of Medical Science, Yazd, Iran, 2015)
Background: Submucous myomas may be associated with menorrhagia, infertility and dysmenorrhea. Objective: The aim of this study was to determine the long term effects of submucousal myoma resection on menorrhagia and infertility; also to detect whether the type, size, and location of myoma affect the surgical success. Materials and Methods: .Totally 98 women referred to hysteroscopy for symptomatic submucousal fibroids (menorrhagia (n=51) and infertility (n=47)) between 2005- 2010 were enrolled in this historical cohort study Pregnancy rates and menstrual improvement rates were compared according to myoma characteristics (size, type and location). Results: After a mean postoperative period of 23±10 months in 51 patients with excessive bleeding, 13 had recurrent menorrhagia (25%). In Other 38 patients excessive bleeding was improved (75%). The improvement rates by location and myoma type: lower segment 100%, fundus 92%, and corpus 63%; type 0) 70%, type 1) 78%, type 2) 80%. The mean sizes of myoma in recurred and improved patients were 23.33 mm and 29.88 mm respectively. 28 of 47 infertile women spontaneously experienced thirty pregnancies (60%). Pregnancy rates according to myoma location and type: lower segment 50%, fundus 57%, and corpus 80%; type 0) 75%, type 1) 62%, type 2) 50%. The mean myoma size in patients who became pregnant was 30.38 mm; in patients who did not conceive was 29.95 mm. Conclusion: The myoma characetesitics do not affect improvement rates after hysteroscopic myomectomy in patients with unexplained infertility or excessive uterine bleeding.